SPIN AND MODEL DETERMINATION OF EXTRA NEUTRAL GAUGE BOSONS AT LHC AND ILC∗ - Pankov, A. A.; Tsytrinov, A. V. (Одеські астрономічні публікації, 2017)
Heavy neutral gauge Z′ bosons are predicted by many models of physics beyond the Standard Model. If a new neutral gauge boson is discovered at the LHC in the clean Drell-Yan channel, the characterization of its spin and couplings will proceed via measuring production rates and angular distributions of the decay products. We study the discrimination between a Z′ boson (spin-1) against the Randall-Sundrum graviton resonance (spin-2) and spin-0 resonance (sneutrino) with the same mass and producing the same number of events in the cross section. The next step would be to measure its properties to identify the underlying theory that gave rise to the Z′. We discuss in this context the foreseeable sensitivity to Z′s of fermion-pair production observables at the ILC with polarized beams, especially as regards the potential of distinguishing diﬀerent Z′ models once such deviations are observed.